1990
DOI: 10.1029/wr026i006p01235
|View full text |Cite
|
Sign up to set email alerts
|

On thermohydrologic conditions near high‐level nuclear wastes emplaced in partially saturated fractured tuff: 1. Simulation studies with explicit consideration of fracture effects

Abstract: We have performed modeling studies on the simultaneous transport of heat, liquid water, vapor, and air in partially saturated, fractured porous rock. Formation parameters were chosen as representative of the potential nuclear waste repository site in the Topopah Spring unit of the Yucca Mountain tuffs. The presence of fractures makes the transport problem very complex, both in terms of flow geometry and physics. The numerical simulator used for our flow calculations takes into account most of the physical effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 28 publications
0
58
0
Order By: Relevance
“…Because very little is known at present about fracture capillary pressures, we consider two cases which are intended to illustrate alternative possible system behavior. Following Pruess et al [1990a], fracture capillary pressure f'ct is parameterized by a simple linear relationship (14) which is constructed so that Pcm (0) =Pet (0) and Pet (1) = f'ct(l) = 0. Note the Pet = 0 for Scril >Strf, so liquid can be mobile in the fractures for a wide range of S1m values.…”
Section: Examples Of F::m (S 1 M) and F'ct (S 1 T) Curves Are Shown Inmentioning
confidence: 99%
“…Because very little is known at present about fracture capillary pressures, we consider two cases which are intended to illustrate alternative possible system behavior. Following Pruess et al [1990a], fracture capillary pressure f'ct is parameterized by a simple linear relationship (14) which is constructed so that Pcm (0) =Pet (0) and Pet (1) = f'ct(l) = 0. Note the Pet = 0 for Scril >Strf, so liquid can be mobile in the fractures for a wide range of S1m values.…”
Section: Examples Of F::m (S 1 M) and F'ct (S 1 T) Curves Are Shown Inmentioning
confidence: 99%
“…There is a long record of mathematical modeling studies devoted to the prediction of the future thermal-hydrological conditions in the unsaturated environment [Nitao et al, 1992;Tsang, 1993, 1994;Pruess et al, 1984Pruess et al, , 1985Pruess et al, , 1988Pruess et al, , 1990aPruess, 1987, 1989]. Typically, these studies have demonstrated that a large, superheated dry rock region will form for several thousand years at Yucca Mountain, and that during this period, infiltrating liquid water is not expected to contact waste packages.…”
Section: Motivationmentioning
confidence: 99%
“…Heat pipes are also expected in the vicinity of the geologic repository for nuclear waste at Yucca Mountain, Nevada (Pruess et al, 1990a(Pruess et al, , 1990b. Determining the magnitude of vapor-liquid counterflow in a heat pipe is relevant to the performance of this repository because the temperature and relative humidity close to the waste packages-important parameters for canister corrosion-are influenced by the relative rates of conductive and convective heat transfer.…”
Section: Introductionmentioning
confidence: 99%